Extraperitoneal versus transperitoneal cesarean section: a prospective randomized comparison of surgical morbidity - Tappauf, Carmen; Schest, Eva; Reif, Philipp; Lang, Uwe; Tamussino, Karl; Schoell, Wolfgang (American journal of obstetrics and gynecology, 2013)
We sought to test the hypothesis that an extraperitoneal cesarean section (ECS) technique reduces postoperative pain without increasing intraoperative and postoperative complications. In a single-center, single-blinded prospective trial we randomized 54 patients with an indication for primary or first repeat cesarean section at term pregnancy to an ECS (n = 27) or transperitoneal cesarean section (TCS) (n = 27) procedure. Patients with suspected abnormal placentation, a history of >1 cesarean section, or major abdominal surgery were excluded. The primary endpoint of the study was maximum abdominal pain measured by numeric rating scale ranging from 0–10. Patients after ECS had significantly less maximum surgical site pain than patients after TCS. Median peak pain scores on postoperative day 1 were 4.00 (interquartile range, 3.00–5.00) for ECS and 5.00 (interquartile range, 4.00–7.00) for TCS, respectively (P = .031). Analgesic requirements, intraoperative nausea, and postoperative shoulder pain were significantly less after ECS. Overall operative time was significantly shorter in ECS, with no difference in delivery time. No bladder injury occurred in either group. There were no differences in estimated blood loss and neonatal outcome. Urogenital distress, urinary tract infection, and bowel dysfunction did not differ at discharge from hospital and 6 weeks after. An extraperitoneal approach to cesarean section appears to reduce postoperative pain, usage of analgesics, and intraoperative nausea without an increase in significant complications.